WITHDRAWN Soft Chemical Synthesis of Nickel-Zinc-Cobalt-Ferrite Nanoparticles and their Structural, Morphological and Magnetic Study at Room Temperature - Parajuli, D.; Vagolu, V.K.; Chandramoli, K.; Murali, N.; Samatha, K. (Journal of Nepal Physical Society, 2021)
This article was withdrawn on 7th April 2025. The withdrawal was carried out at the request of the journal’s editor and the corresponding author.